Combination impacts of gamma radiation and low temperature on the toxin‐producing Bacillus cereus isolated from fried and steam rice. Issue 12 (3rd November 2021) - Munshi, Md. Kamruzzaman; Sukhi, Farzana Akter; Huque, Roksana; Hossain, Arzina; Mahbub, Shamim; Ariful Hoque, Sheikh; Hossain, Tania; Khan, Md. Shafiqul Islam; Hossain, Md. Fuad
Abstract: Thirty randomly collected steam and fried rice sample from Dhaka City were investigated for toxin‐producing Bacillus cereus to observe the antibiotic sensitivity and survival ability of the toxic strain in combination treatment of gamma radiation and low temperature. Twenty‐nine strains of Bacillus spp. were isolated and seven strains were confirmed as pathogenic B. cereus . A known toxic strain KTCC 11, 204 and seven pathogenic strains were subjected to cytotoxic effect analysis using Vero cell through protein estimation. KTCC 11, 204 and one toxic B. cereus strain was treated by gamma radiation at 4, 6 and 8 kGy dose and 4°C temperature for three consecutive days. At third day of storage, Toxic B. cereus count was significantly low and totally eliminated at 8 kGy dose during all storage period. The toxic B. cereus was further tested against 10 antibiotics and found highly sensitive to imipenem, penicillin, amoxycillin, ampicillin, and chloramphenicol. Novelty Impact statement: Toxin‐producing Bacillus spp. were isolated from steam and fried rice sample. The toxic B. cereus was found highly sensitive to imipenem, penicillin, amoxycillin, ampicillin, and chloramphenicol. Different doses of gamma ray and 4°C temperature result in a significant reduction of toxic B. cereus count.